2010
DOI: 10.2169/internalmedicine.49.3381
|View full text |Cite
|
Sign up to set email alerts
|

Transient Polyuria Related to Central Diabetes Insipidus Caused by Lymphocytic Infundibulo-neurohypophysitis in a Patient Treated for Graves' Disease

Abstract: A 45-year-old man was hospitalized because of weight loss, finger tremor, thirst, polydipsia and increased urinary frequency. He was diagnosed with Graves' disease (GD) and central diabetes insipidus (CDI). Magnetic resonance imaging revealed the enlarged posterior pituitary with thickened stalk. Histological examination obtained from biopsy of the pituitary revealed lymphocytic infundibulo-neurohypophysitis. He received treatment with thiamazole (MMI) for GD and desmopressin acetate (DDAVP) for CDI. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…A similar complicated case, but with a transient course of central DI, was reported by Yamazaki et al ( 9 ) showed interesting findings that may prompt reconsideration of our case. A middle-aged man diagnosed with Graves' disease and central DI had received treatment with thiamazole.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…A similar complicated case, but with a transient course of central DI, was reported by Yamazaki et al ( 9 ) showed interesting findings that may prompt reconsideration of our case. A middle-aged man diagnosed with Graves' disease and central DI had received treatment with thiamazole.…”
Section: Discussionsupporting
confidence: 81%
“…Recent research has also provided evidence that rabphilin-3A is a major autoantigen for LINH and thus might be useful as a biomarker for the diagnosis of central DI ( 8 ). Clinical relationships have been detected between LINH and other diseases, including autoimmune thyroiditis ( 9 ), systemic lupus erythematosus ( 10 ) and Behçet's disease ( 11 ) as well as a drug-induced case ( 12 ). However, the complication of DI secondary to thyroid storm has not been well documented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 However, according to different autopsy series occurrence of aHYP could also been shown in males. 4 aHYP most commonly presents with symptoms of sellar mass with or without varying degrees of hypopituitarism, whereas DI is uncommon.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphocytic hypophysitis rarely associated with Graves’ disease may cause central diabetes insipidus which may present with polyuria in such a setting. [4] This was ruled out by a negative water deprivation test in our patient.…”
mentioning
confidence: 83%